Pengembangan Buku Cerita Berbasis Pendidikan Karakter pada Ranah Sekolah bagi Siswa SMP Kelas VII di Kabupaten Kendal - Handayani, Lestari; Mujimin, Mujimin; Purnomo, Sucipto Hadi (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2020)
This research aims to develop story books as a means for students to learn Javanese independently. It also can be useful for teachers in instilling character values ​​through stories. This research uses research and development methods, with five stages of research consisting of identification of potential and problems, data collection, product design, design validation, design revision. Data collection using observation techniques, interviews, questionnaires, and expert assessment sheets. The results of the study are story books that were designed using Corel Draw X7, Adobe Illustrator, and Photoshop. This story book contains eight story subtitles that raise issues faced by students at school. The results of the validation showed that there were improvements and suggestions that needed to be done, namely diction, flow, background description, thematic focus and added humor. Scoring of the product also exceeds the minimum limit, so the product can be said to be feasible.